Kistler Home Page (1999)
Kistler Instrument Corporation Home Page. Kistler designs and produces high-quality instruments for measuring pressure, force, acceleration and strain. Because of the company's extensive research and development program, Kistler's measuring instruments have achieved a leading position worldwide. These instruments have found thousands of applications providing reliable and precise measurement results. Kistler can deal with challenging measurement problems and will find solutions which best meet our customer's needs.